Associations of components of sarcopenic obesity with bone health and balance in older adults. (March 2018) - Scott, David; Shore-Lorenti, Catherine; McMillan, Lachlan; Mesinovic, Jakub; Clark, Ross A.; Hayes, Alan; Sanders, Kerrie M.; Duque, Gustavo; Ebeling, Peter R.
Highlights: Higher muscle mass is a consistent independent predictor of better bone health in community-dwelling older men and women. Higher body fat percentage does not appear to be beneficial for bone health. Reduced lower-leg muscle density is independently associated with lower cortical density and area in obese older women. Reduced lower-leg muscle density is associated with poorer balance in both sexes. Abstract: Objectives: To determine characteristics of sarcopenic obesity that are independently associated with bone health and balance in older adults. Study design: Cross-sectional study of 168 community-dwelling older adults (mean age 67.7 ± 8.4 years; 55% women). Main outcome measures: Appendicular lean mass (ALM), whole-body areal BMD (aBMD) and body fat percentage were assessed by dual-energy X-ray absorptiometry. Peripheral quantitative computed tomography assessed muscle density and cortical volumetric BMD (vBMD), area, thickness, and strength-strain index (SSI) at 66% tibial length. Hand grip strength (dynamometry) and balance path length (computerised posturography) were assessed. Obesity was defined as high body fat percentage. Results: Greater lower-leg muscle density was associated with lower balance path length in men (r = −0.36; P < .01) and women (r = −0.40; P = < .01). Obese participants by body fat percentage did not differ to non-obese on bone indices, although a trend towards lower cortical vBMD was observed in obese compared with non-obese men (1041.4 ± 39.8 vs 1058.8 ± 36.1 mg/cm 3 ; P = .051). In multivariable models, ALM was positively associated with all bone parameters in obese women, and with whole-body aBMD, proximal tibial cortical area and SSI in non-obese women, and both non-obese and obese men (all P < .05). Lower-leg muscle density was also positively associated with cortical vBMD (B = 2.91; 95% CI 0.02, 5.80) and area (2.70; 0.06, 5.33) in obese women. Conclusions: Amongst components of sarcopenic obesity, higher ALM is a consistent independent predictor of better bone health. Low muscle density may also compromise bone health and balance. Interventions which improve muscle mass and composition may lower fracture risk in sarcopenic obesity.